Increased water intake to reduce headache: learning from a critical appraisal. - Price, A; Burls, A (Wiley, 2015)
Critically Appraised Topic (CAT): Water Intake to Reduce Headache Clinical Bottom Line Water intake is a cost effective, non-invasive and low-risk interven-tion to reduce or prevent headache pain. Rationale: Chronic mild dehydration may triggerheadache. Increased water intake could help. A small trial shows modest benefit; however,a larger methodologically sound randomized controlled trial is needed to confirm efficacy.Critically Appraised Paper Spigt, M., Weerkamp, N., Troost, J., van Schayck, C. P., and Knottnerus, J. A. (2012). ‘A randomized trial on the effects of regular water intake inpatients with recurrent headaches.’Family practice,29(4), 370–5. Doi: 10.1093/fampra/cmr112Clinical scenarioPatients from primary care registered as ‘headache’, ‘tension headache’and/or ‘migraine’ for more than one year who suffer at least two episodes of moderately intense headache or more than four mildly intense episodes of headache per month with a daily fluid intake of less than 2.5 litres per day.PICO (M)Patient/Problem=Headache>1 year with 2 moderately intense or 4 mildly intense episodes per month Intervention=1.5 litres water per day+stress control and sleep hygiene Comparison/Control=stress control and sleep hygiene Outcome=Reduce or eliminate headache Methodology=Therapy RCTTable 1:Final Search TermsTRIP Data Base:hits = 517used filter ExtendedPrimary research 4 found1 paper applicable’Water intake ’[MeSHTerms] AND ’Headache’[All Fields]’Best match toPICO, (2012) RCTSelection Criterion and Overall Results102 headache patients in 16 primary care clinicswere randomized into control (n=50) and intervention groups (n=52) Inclusion cri-teria=two>episodes of moderately intense headache or five>mildly intense headaches per month and total fluid intake>2.5 litres per day, Follow-up @ 3 months. 79% inter-vention and 66% of controls completed RCT. Drinking more water resulted in a statisticallysignificant improvement of 4.5 (confidence interval: 1.3–7.8) points on Migraine-Specific Quality of Life (MSQOL). 47% in the intervention (water) group self-reported improve-ment (6>on a 10-point scale) against 25% in controls. Drinking water did not reduce headache days.Comments The transparency from the author of this critically appraised paper enables others to use this study as a teaching tool and to learn from the shortcomings in the trial.The study was underpowered and contains methodological shortcomings. Participants were partially un-blinded during the trial increasing the risk for bias. Only the subjective measures are statistically significant and attrition was significant. The intervention is low risk and of negligible cost. A methodologically sound RCT is recommended to evaluate if the intervention has beneficial effects.